Geomorphology and Karstification of the Southern Field High Carbonates in Central Luconia Province - Chung Wei Kiat, David Menier, SN Jamaludin, Deva Ghosh, . (2016)
The development of the Central Luconia carbonates in offshore Sarawak has been governed by the orientation of the Luconia Platform, syn-depositional features generated by the rifting and oceanographic parameters, such as sea level fluctuations, hydrodynamic, climate changes, salinity, and oxygen levels. The studied carbonate platform is developed over a southern field high of Central Luconia Province.